2016
DOI: 10.1007/s00431-016-2768-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between childcare and risk of childhood overweight and obesity in children aged 5 years and under: a systematic review

Abstract: • Lifestyle factors during early years affect health outcomes in adulthood, particularly in children with low birth weight. • Pre-school stage influences children's body composition and growth. What is new: • This is the first systematic review of observational studies examining the association between childcare and childhood overweight and obesity in preschool children. • 'Informal' care is linked to early introduction to solid foods, less physical activity and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 25 publications
1
60
1
3
Order By: Relevance
“…To discover the potential relationships between BMI and other markers against galectin-3 at a young age is important because of the increased risk of developing obesity in adulthood and the likelihood of serious short-term and long-term health problems in obese children and adolescents (24,25). In this respect, our study data in adolescents makes it difficult to establish a relationship between the levels of obesity and galectin-3 observed in this group.…”
Section: Discussionmentioning
confidence: 80%
“…To discover the potential relationships between BMI and other markers against galectin-3 at a young age is important because of the increased risk of developing obesity in adulthood and the likelihood of serious short-term and long-term health problems in obese children and adolescents (24,25). In this respect, our study data in adolescents makes it difficult to establish a relationship between the levels of obesity and galectin-3 observed in this group.…”
Section: Discussionmentioning
confidence: 80%
“…Broadly, those authors suggest CBC may protect against overweight by promoting a healthier diet and providing health care [62]. Yet other studies have found no association between CBC and childhood overweight [67][68][69][70][71][72][73][74]. Attending CBC could be associated with lower risk of child overweight or obesity through several pathways, including planned nutritional programs and learning environments, healthy eating, regular opportunities for physical activity, regular bedtime and rise time, and reduced screen time (eg, computers, mobile phones, television) [62,63,75,76].…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…Two of the studies included in Alberdi et al . 's () systematic review were conducted in the UK (Pearce et al . ; Tanskanen ).…”
Section: Weight Gain During the Preschool Years And Childcare Exposurementioning
confidence: 99%
“…The second study of UK data included in Alberdi et al . 's () systematic review used the same data set as Pearce et al . () to explore whether the contribution of grandparental childcare to increased risk of childhood overweight and obesity was dependent on the lineage of the grandparent ( i.e .…”
Section: Weight Gain During the Preschool Years And Childcare Exposurementioning
confidence: 99%
See 1 more Smart Citation